Assessment of maternity protection among healthcare workers in GhanaAJOG Global Reports at a Glance - Joycelyn Darkwah, MD, MPH; Augustina Koduah, BPharm, MSc, PhD (AJOG Global Reports)
Background: Female workers who are pregnant or breastfeeding require adequate support to balance their roles as mothers and employees. This support comes in the form of Maternity Protection (MP). Low maternity protection among female workers is a major public health concern. Less research has been done on all the components of MP, especially among healthcare workers in Ghana. Objective: The study aims to assess maternity protection as a whole (all the components of maternity protection) among female healthcare workers (HCWs) in health facilities in the Agona West District of Ghana. Study design: A descriptive cross-sectional study involving 102 female workers in all the health facilities in the Agona West District of Ghana was conducted. A multistage sampling technique was employed. The International Labour Organization (ILO) standard questionnaire (adapted) was administered to assess all components of MP such as maternity leave, cash benefits, health protection at work, employment and discrimination, and childcare arrangements. Results: All (100%) participants stated that they had paid maternity leave but 7.8% received less than the 12-week statutory maternity leave. 23.5% felt that their health and that of their child were at risk due to work. Regarding employment and discrimination, none of them were dismissed due to pregnancy or childbirth. However, 2 % did not get their due promotion and 12.7% stated that they received unpleasant comments related to pregnancy or birth. Concerning breastfeeding, 82.4% of all the HCWs were able to breastfeed for at least 6 months whilst among all the HCWs, 17.6% were able to breastfeed whilst at work. 25% of the HCWs were somewhat satisfied with their childcare arrangements. Conclusion: Maternity Protection among female healthcare workers in health facilities in Agona West District is moderate. The roles of pregnant or nursing mothers in the workplace should be adapted to their health needs, promoting a healthy work environment. This study recommends that the heads of the health facilities and all stakeholders ensure maternity protection through education, awareness, and review of workplace policies as well as establish control measures for those who flout this policy.